Development and fecundity of Sesamia calamistis (Lepidoptera: Noctuidae) and Eldana saccharina (Lepidoptera: Pyralidae) - Shanower, T.G.; Schulthess, F.; Bosque-Perez, N. (1993)
The developmental rates and fecundity of two important African maize pests, Sesamia calamistis Hampson and Eldana saccharina Walker, were studied under constant temperatures and with two larval diets. Five temperatures (15°, 20°, 25°, 30° and 35°C) were used to investigate developmental rates and three temperatures (20°, 25° and 30°C) were used in fecundity experiments. Larvae were reared on maize stem cuttings and on artificial diet. The developmental period for S. calamistis on artificial diet required over 700 degree-days (DD); eggs needed 122 DD above a threshold of 9.7°, larvae required 383 DD above 12.2°C and pupae 204 DD above 10.2°C. The developmental period for E. saccharina on artificial diet was 665 DD; eggs required 125 DD above 9.1°C, larvae 400 DD above 10.6°C and pupae 140 DD above 8.8°C. On artificial diet both species developed faster and had higher threshold temperatures for larval development than when reared on maize stem cuttings. Pupal development rates did not differ between artificial diet and maize stem for either species, although developmental thresholds were marginally lower on artificial diet. S. calamistis averaged 250–690 eggs/female although some individuals produced more than 1000 eggs. Adult females lived 5.7 days at 30°C and 10 days at 20°C. E. saccharina females produce more eggs and lived longer than S. calamistis females. Average fecundity for E. saccharina was 470–620 eggs/female, but several individuals produced more than 1200 eggs. Adult females lived 6.6 days at 30°C and 14.6 days at 20°C.